ANALISIS PERANCANGAN SISTEM MONITORING PRAKTIK KERJA LAPANGAN SISWA SMK JURUSAN TEKNIK KOMPUTER DAN JARINGAN (TKJ) - Syahputri, Nita; Andriani, Nova; Tahel, Fithry; Nurhayati, Nurhayati (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2025)
Field Work Practice (PKL) is one of the most important activities in the Vocational High School (SMK) education curriculum, because this activity provides an opportunity for students to connect and apply the theoretical knowledge they gain in school to direct practice in the industrial world. This research aims to analyze the existing problems and design a web-based PKL monitoring system that is more efficient and can facilitate better interaction between schools, students, and industry supervisors. The system development method used in this research is the waterfall method, which consists of clear stages starting from analyzing system requirements, designing interfaces, coding, to testing and implementation stages. The results show that with this web-based street vendor monitoring system, efficiency in reporting and supervising street vendor activities can be significantly improved. This system also facilitates transparency in every stage of PKL implementation, making it easier for schools to evaluate and manage data related to students undergoing PKL.